2018
DOI: 10.1002/pros.23644
|View full text |Cite
|
Sign up to set email alerts
|

Statin use, high cholesterol and prostate cancer progression; results from HCaP‐NC

Abstract: Statin use at diagnosis was not associated with prostate cancer progression in the population-based, minority-enriched HCaP-NC. Greater healthcare engagement, including actively controlling serum cholesterol, may be linked to better prostate cancer-specific outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…After carefully reading the titles/abstracts, most studies were excluded because they were reviews (n=11), non-human studies (n=6), or obviously not related with our topic (n=121). After assessing the full-text of 18 potentially relevant articles, we identified 12 eligible studies,915,17,2326 including 13 data sets for analysis; 1 study9 reported the results separately by racial differences. The main reasons for exclusion were as follows: duplicate reports (n=1), no data on exposure (n=1), and no data on outcome of interest (n=4).
Figure 1Flow diagram of literature search process.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After carefully reading the titles/abstracts, most studies were excluded because they were reviews (n=11), non-human studies (n=6), or obviously not related with our topic (n=121). After assessing the full-text of 18 potentially relevant articles, we identified 12 eligible studies,915,17,2326 including 13 data sets for analysis; 1 study9 reported the results separately by racial differences. The main reasons for exclusion were as follows: duplicate reports (n=1), no data on exposure (n=1), and no data on outcome of interest (n=4).
Figure 1Flow diagram of literature search process.
…”
Section: Resultsmentioning
confidence: 99%
“…of casesAge (years)Exposure (no. )Rate of recurrenceAllott et al (black)92016USARMedian: 32.4628Mean: 59.7 (SD: 6.4)TC (46), LDL (46), HDL (188), TG (92)181 (29%)Allott et al (non-black)92016USARMedian: 361020Mean: 62.3 (SD: 5.8)TC (69), LDL (88), HDL (433), TG (182)272 (27%)Allott et al232018USAPMedian: 45.6669Range: 40–79TC (425)138 (21%)Bhindi et al242016CanadaPMedian: 311939Mean: 61.5 (SD: 6.9)HDL (NR), TG (NR)NRKang et al132015KoreaRMedian: 21663Median: 68 (IQR: 62–72)TG (109)66 (10%)Komaru et al122010JapanRMedian: 35173Median: 65 (SD: 5.1)TC (NR)NRMacleod et al102015USARMedian: 411706NRLDL (440), HDL (1174), TG (736)279 (16%)Ohno et al172016JapanRMean: 54.0562Mean: 65....…”
Section: Resultsmentioning
confidence: 99%
“…Statin use was found to be associated with lower risks of primary liver cancer (McGlynn et al, 2015), hepatocellular carcinoma (Kim et al, 2018), HPV-negative squamous cell carcinoma (SCC) of the larynx, hypopharynx, and nasopharynx (Lebo et al, 2018), and subtypes of non-Hodgkin lymphomas including diffuse large B-cell lymphomas and plasma cell lymphomas (Ye et al, 2018), reduced aggressiveness (Allott et al, 2016) and mortality (Yu et al, 2014) of prostate cancer, and lower cancer specific and all-cause mortalities in esophageal cancer (Nguyen et al, 2018). However, statins do not affect survival after colorectal cancer (Hoffmeister et al, 2015) and small-cell lung cancer (Seckl et al, 2017), the risk of pancreatic cancer (Hamada et al, 2018), or the progression of prostate cancer in certain minority-enriched subpopulations (Allott et al, 2018). The type and hydrophilicity of statins, length of statin use, and ethnicity, lifestyle, and preexisting health condition of subjects may have contributed to the diverse outcome in statin and cancer studies—with some but not all studies showing the anticancer effect of statins (Gong et al, 2017).…”
Section: Effects Of Statins On Cancer Growth With Dose-limiting Toxicmentioning
confidence: 99%
“…Findings from several retrospective observational studies indicate that treatment with statins or metformin can reduce prostate-specific antigen (PSA) levels 48. Statin use is found to be associated with a lower advanced prostate cancer risk and reduced prostate cancer-specific mortality 9. Statins are potent inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase, and are commonly used for treating hyperlipidemia by lowering cholesterol 9,10.…”
Section: Introductionmentioning
confidence: 99%
“…Statin use is found to be associated with a lower advanced prostate cancer risk and reduced prostate cancer-specific mortality 9. Statins are potent inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase, and are commonly used for treating hyperlipidemia by lowering cholesterol 9,10. Cholesterol plays a role in steroid androgens that drive prostate growth 11.…”
Section: Introductionmentioning
confidence: 99%